On some aspects of control in the context of complexity - Wyciślak, Sławomir (Journal of Public Governance, 2014)
The paper begins with an overview of complexity evolution, its nature and types. The author discusses e.g. the characteristics of epistemological, dynamic and computational complexity. Next, he describes the evolution of the system approach in the context of complexity mastering. He then focuses on the problem of control. Self-control and modularity are considered as the conditions of complexity control in a global system. To master complexity, one needs absorbers, i.e. values identified within the system. A framework in which absorbers can be created is provided by the agents’ subjectivity. Different variants of modules have been identified with reference to agent subjectivity, and his or her reflexivity and inertia.